Optimalisasi Penyusunan Panduan Asuhan Keperawatan di Unit Hemato Onkologi - Vivin Ari S; Laode Abdul Rahman; Yuni Susiana Nur (Jurnal Keperawatan Silampari, 2022)
This study aims to optimize the preparation of nursing care guidelines in the Hemato Oncology unit of RS X Bogor City. The method used in this research is a pilot project. The results showed that the majority of the ages were in the age range of 21-30 years, 85%, with the majority being female, as much as 80%. The competency level of nurses for pre-PK has the highest percentage at 40%. The length of work of nurses in the hemato-oncology unit is 2-5 years, as much as 60%. Respondents are implementing nurses as much as 95% and D3 education as much as 75%. The training qualification for implementing nurses that must be followed is BTCLS (Basic Trauma Cardiac Life Support) training. All nurses in the unit have attended as many as 95.24%. This research resulted in formulating an innovative nursing care guide in the Hematology-Oncology Unit. The focus was compiled because the preparation of nursing care guidelines at Hospital X Bogor City was not optimal, especially for cases in the Hematology-Oncology Unit. In conclusion, the nursing care guide becomes a guideline that will be used in determining care for patients who will bridge the nursing profession in preparing nursing care plans, especially in cases of hemato-oncology. Keywords: Integrated Collaboration, Nursing Care Guide